2022
DOI: 10.1097/aog.0000000000004652
|View full text |Cite|
|
Sign up to set email alerts
|

Universal Hepatitis B Antibody Screening and Vaccination in Pregnancy

Abstract: OBJECTIVE: To evaluate the cost effectiveness of universal screening for hepatitis B immunity and vaccination among pregnant women in the United States. METHODS: We designed a decision-analytic model to evaluate the outcomes, costs, and cost effectiveness associated with universal hepatitis B virus (HBV) immunity screening in pregnancy with vaccination of susceptible individuals compared with no screening. A theoretical cohort of 3.6 million women, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This result reflects the worldwide statistics, which estimate that only 39% of infants receive the vaccine birth dose (9), despite the WHO recommendations. Cost‐benefit analysis has induced health care authorities of several countries with low endemicity not to vaccinate infants at birth if the screened mother is HBsAg negative (21) Indeed, this strategy can be very effective to identify newborns in need of HBV‐immunization (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…This result reflects the worldwide statistics, which estimate that only 39% of infants receive the vaccine birth dose (9), despite the WHO recommendations. Cost‐benefit analysis has induced health care authorities of several countries with low endemicity not to vaccinate infants at birth if the screened mother is HBsAg negative (21) Indeed, this strategy can be very effective to identify newborns in need of HBV‐immunization (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…Prabhu et al conducted a cost–effectiveness analysis among pregnant women in the USA and found that universal HBV immunity screening and vaccination of susceptible individuals is cost–effective compared to no screening and vaccinating routinely. 24 Although most countries have screened for high-risk groups, the diagnosis rates remain low. In order to resolve this issue, MehlikaUniversal HBsAg screening of adults for chronic hepatitis B(CHB) in the general population of the USA was carried out and found to be cost–effective and potentially cost-saving compared to the current CHB screening recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant patients should be screened for hepatitis B virus infection at the first prenatal visit of each pregnancy (12,(26)(27)(28). The HBsAg test should always be performed regardless of prior vaccination.…”
Section: Moderate-quality Evidence)mentioning
confidence: 99%